Direct and inderect perpetrator of crime: new scientific view on their legislative regulation - Kovalchuk, Aleksey V. (Journal of the Belarusian State University. Law, 2019)
The article illustrates the narrow approach of legislative regulation in art. 16 of the Criminal Code of the Republic of Belarus of the perpetrator of crime, which is one of the types of accomplices in a crime. It is argued that, in part 3 of art. 16 of the Criminal Code of the Republic of Belarus, fixing the direct perpetrator of crime, the legislator did not fully reflect who is understood as a co-perpetrator, and who the person who committed the crime, along with other types of accomplices who are not perpetrators, understood. It is substantiated that the use by the perpetrator of persons who are subject to criminal responsibility and those not subject to such for the commission of a crime have a different legal nature and it is not acceptable to generalize them into an independent institution of complicity in a crime. For a more precise differentiation of criminal responsibility, the author’s vision of the formulation of norms in the Criminal Code, regulating the direct and inderect perpetrator of a crime, is proposed.